2014
DOI: 10.1038/srep06495
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated networks underlie immune response regulation in papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is a common endocrine malignancy with low death rate but increased incidence and recurrence in recent years. MicroRNAs (miRNAs) are small non-coding RNAs with diverse regulatory capacities in eukaryotes and have been frequently implied in human cancer. Despite current progress, however, a panoramic overview concerning miRNA regulatory networks in PTC is still lacking. Here, we analyzed the expression datasets of PTC from The Cancer Genome Atlas (TCGA) Data Portal and demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…28 Recently, it has been suggested that its oncogenic effect in PTC involves activation of the PI3K/Akt/Bad pathway, 29 which is consistent with it having a master regulator role. Moreover, both miR-34a and -221 have been very recently identified in the TCGA data set as crucial regulators of the immune response activities among all papillary carcinoma variants studied by this consortium, 19 further confirming our results.…”
Section: Modern Pathology (2015) 28 748-757supporting
confidence: 90%
See 1 more Smart Citation
“…28 Recently, it has been suggested that its oncogenic effect in PTC involves activation of the PI3K/Akt/Bad pathway, 29 which is consistent with it having a master regulator role. Moreover, both miR-34a and -221 have been very recently identified in the TCGA data set as crucial regulators of the immune response activities among all papillary carcinoma variants studied by this consortium, 19 further confirming our results.…”
Section: Modern Pathology (2015) 28 748-757supporting
confidence: 90%
“…12,[14][15][16][17] However, little data are available on downregulated miRNAs, or on the changes present in less frequent histological subtypes such as follicular tumors. It is also important to highlight that apart from recent miRNA deepsequencing studies using papillary tumors, 16,18,19 the remaining data on deregulated miRNAs in thyroid cancer were generated at a time when only~300 miRNAs had been identified, compared with thẽ 1300 miRNAs that are known today. 11 We have performed a miRNA deep-sequencing study using the largest collection of thyroid samples published to date, comprising of 127 thyroid tumors (including 26 follicular adenomas, 23 follicular carcinomas and 78 papillary thyroid carcinomas) and 17 normal thyroid tissues.…”
mentioning
confidence: 99%
“…We demonstrate for the first time that NIS is posttranscriptionally modulated by miRNAs in thyroid cancer. Very recently, it has been shown that miR-339 modulates NIS expression in rat normal thyroid cells (37), yet this miRNA has not been shown to be deregulated in thyroid cancer in previous studies including ours (16,38,39). We consistently show that miR-146b-3p binds to the 3 0 -UTR of NIS (site 3-9 nt), leading to an impaired translation of the protein and subsequently decreasing the iodide uptake of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…The first study performing next-generation sequencing of miRNAs in PTC mainly focused on isomer analysis (39). In another recent study, Huang and colleagues (38) analyzed the miRNAs expression datasets of PTC from TCGA Data Portal. The authors emphasized that immune responses are significantly enriched and under specific regulation in the direct miRNA-target network, but miRNAs regulating thyroid differentiation genes were not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which individual miRNAs regulate common processes of tumor biology across diverse cancer types is beginning to be known and new examples of miRNAs that coordinately regulate cancer pathways (i.e., DNA demethylation pathway members) are emerging (35). Genomic analysis of PTC tumors in TCGA clearly suggests that miRNA expression patterns (36). The authors emphasized that immune responses are significantly enriched and under specific regulation in the direct miRNA-target network.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 99%